Effect of crystallization kinetics on the properties of spray dried microparticles. Issue 7 (2nd July 2016) - Baldelli, Alberto; Power, Rory M.; Miles, Rachael E. H.; Reid, Jonathan P.; Vehring, Reinhard
ABSTRACT: A droplet chain technique was used to study the influence of the crystallization process on the morphology of spray dried microparticles. A piezoceramic dispenser produced a chain of monodisperse solution droplets with an initial diameter in the range of 60–80 µm. Aqueous solutions of sodium nitrate were prepared in concentrations ranging from 5 mg/ml to 5⋅10 −5 mg/ml. The solution droplets were injected into a laminar flow with gas temperatures varying from 25 to 150°C, affecting the droplet temperature and the evaporation rate, accordingly. Dried particles with diameters between 0.3 and 18 µm were collected. The properties of the collected microparticles were studied and correlated with a particle formation model which predicted the onset of saturation and crystallization. The model accounted for the dependence of the diffusion coefficient of sodium nitrate in water on droplet viscosity. The viscosity trend for sodium nitrate solutions was determined by studying the relaxation time observed during coalescence of two aqueous sodium nitrate droplets levitated in optical tweezers. The combination of theoretical derivations and experimental results showed that longer time available for crystallization correlates with larger crystal size and higher degrees of crystallinity in the final microparticles. Copyright © 2016 American Association for Aerosol Research